2012
DOI: 10.1007/s10461-012-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

Streaming Weekly Soap Opera Video Episodes to Smartphones in a Randomized Controlled Trial to Reduce HIV Risk in Young Urban African American/Black Women

Abstract: Love, Sex, and Choices is a 12-episode soap opera video series created as an intervention to reduce HIV sex risk. The effect on women's HIV risk behavior was evaluated in a randomized controlled trial in 238 high risk, predominately African American young adult women in the urban Northeast. To facilitate on-demand access and privacy, the episodes were streamed to study-provided smartphones. Here, we discuss the development of a mobile platform to deliver the 12-weekly video episodes or weekly HIV risk reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 55 publications
0
66
1
5
Order By: Relevance
“…Empirically based media prevention interventions using efficacious communication techniques may have the greatest (Horner et al, 2008;Jones & Lacroix, 2012;Major & Coleman, 2012;Medina & Rios, 2011;Romer et al, 2009;Sznitman, Stanton, et al, 2011;. Younger-aged women are influenced significantly by mass media (J. D. Brown et al, 2005); yet there are few research studies reported on the association of communication systems and interpersonal relationships in college females.…”
Section: Media Interpersonal Communication and The Female College Smentioning
confidence: 99%
“…Empirically based media prevention interventions using efficacious communication techniques may have the greatest (Horner et al, 2008;Jones & Lacroix, 2012;Major & Coleman, 2012;Medina & Rios, 2011;Romer et al, 2009;Sznitman, Stanton, et al, 2011;. Younger-aged women are influenced significantly by mass media (J. D. Brown et al, 2005); yet there are few research studies reported on the association of communication systems and interpersonal relationships in college females.…”
Section: Media Interpersonal Communication and The Female College Smentioning
confidence: 99%
“…A more complete discussion of the theoretical framework is available (Jones, 2006; Jones et al, 2013; Jones & Oliver, 2007). The clinical trial evaluating LSC on women's HIV sex risk behavior was conducted with 238 high-risk, mostly Black women, ages 18 to 29, in the urban Northeast (Jones et al, 2013; Jones & Lacroix, 2012). The comparison group received 12 weekly, text-based HIV prevention messages.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of LSC indicated that viewers had identified with characters, wanted the series to continue, and wanted their friends to watch (Jones & Lacroix, 2012). However, subsequent focus groups determined that viewers needed greater emphasis to identify important health promotion messages because they had become so immersed in the storyline.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations